Pengaruh Segmentasi Pasar, Desain Kemasan dan Strategi Iklan terhadap Minat Beli Konsumen - Aslam, Ahmad Suhail; Nurman, Muhamad; Irawan, Anggi (SAFE-Network, 2025)
This study aims to analyze the influence of market segmentation, packaging design, and advertising strategies on consumers’ purchase intention of Joy Tea Green, a new product by PT Sinar Sosro Jakarta. The research background highlights the growing competition in the ready-to-drink tea industry, which demands appropriate marketing strategies. This study uses a quantitative approach with a survey method and multiple linear regression analysis. The data was collected from 96 purposively selected consumers who had known or seen the Joy Tea Green product. The findings show that market segmentation, packaging design, and advertising strategies positively and significantly affect purchase intention both simultaneously and partially. These results offer practical contributions for PT Sinar Sosro in formulating targeted and efficient marketing strategies and provide insights for other industries to understand consumer behavior in launching new products.